Wing size but not wing shape is related to migratory behavior in a soaring bird - Graña Grilli, Maricel (2017)
Both wing size and wing shape affect the flight abilities of birds. Intra and inter-specific studies have revealed a pattern where high aspect ratio and low wing loading favour migratory behaviour. This, however, have not been studied in soaring migrants. We assessed the relationship between the wing size and shape and the characteristics of the migratory habits of the turkey vulture Cathartes aura, an obligate soaring migrant. We compared wing size and shape with migration strategy among three fully migratory, one partially migratory and one non-migratory (resident) population distributed across the American continent. We calculated the aspect ratio and wing loading using wing tracings to characterize the wing morphology. We used satellite-tracking data from the migratory populations to calculate distance, duration, speed and altitude during migration. Wing loading, but not aspect ratio, differed among the populations, segregating the resident population from the completely migratory ones. Unlike what has been reported in species using flapping flight during migration, the migratory flight parameters of turkey vultures were not related to the aspect ratio. By contrast, wing loading was related to most flight parameters. Birds with lower wing loading flew farther, faster, and higher during their longer journeys. Our results suggest that wing morphology in this soaring species enables lower-cost flight, through low wing-loading, and that differences in the relative sizes of wings may increase extra savings during migration. The possibility that wing shape is influenced by foraging as well as migratory flight is discussed. We conclude that flight efficiency may be improved through different morphological adaptations in birds with different flight mechanisms.